Optimalisasi Peran Penegak Hukum Dalam Upaya Pencegahan Praktik Korupsi Di Indonesia - I Putu Nanda Pramudya; Wahyudi (NAAFI: JURNAL ILMIAH MAHASISWA, 2025)
Corruption in Indonesia remains a systemic problem that undermines national development, necessitating an optimal role from all law enforcement agencies in prevention efforts. This study aims to analyze and optimize the role of law enforcement institutions such as the Police, Attorney General's Office, Corruption Eradication Commission (KPK), and the Courts in developing more effective corruption prevention strategies. The research method employed is a qualitative literature study, analyzing various literature, regulations, and performance data of law enforcement institutions related to preventive measures. The discussion results indicate that optimizing this role requires strong synergy, structured coordination, and transparency among law enforcement agencies, as well as strengthening preventive aspects through anti-corruption socialization, education, and bureaucratic reform. It is concluded that corruption prevention relies not only on repressive measures but more on the effectiveness of preventive steps carried out integratively by all law enforcement stakeholders. This study recommends establishing a technology-based data integration and monitoring system and enhancing human resource capacity to support more comprehensive prevention efforts.